Alpha-DBL: A Reasonable High Secure Double-Block-Length Hash Function - Linh, Hoang Dinh; Thai, Tran Hong (Journal of Science and Technology on Information security, 2021)
Abstract—We propose a new double-block-length compression function which is called Alpha-DBL. This scheme uses two parallel secure single block length schemes based on a block cipher with -bit key and -bit block size to compress a -bit string to a -bit one. We show that the Alpha-DBL scheme attains nearly optimal collision security and preimage security bounds (up to and queries for finding a collision and a preimage, respectively). More precisely, for , no adversary making less than queries can find a collision with probability greater than 1/2. To our knowledge, this collision security bound is nearly better than other such compression functions. In addition, we provide a preimage security analysis of Alpha-DBL that shows security bound of queries for . Using this scheme in the iterated hash function construction can preserve the collision resistance security and the preimage resistance security. Tóm tắt—Chúng tôi đề xuất một hàm nén độ dài khối kép mới được gọi là Alpha-DBL. Lược đồ này sử dụng hai lược đồ độ dài khối đơn an toàn song song dựa trên mã khối với khóa -bit và kích thước khối -bit để nén chuỗi -bit thành chuỗi -bit. Chúng tôi đã chứng minh rằng, lược đồ Alpha-DBL đạt được cận an toàn kháng va chạm và kháng tiền ảnh gần như tối ưu (tối đa và truy vấn tương ứng để tìm va chạm và tiền ảnh). Cụ thể với , một kẻ tấn công bất kỳ thực hiện ít hơn truy vấn chỉ có thể tìm thấy một va chạm với xác suất nhỏ hơn 1/2. Theo hiểu biết của chúng tôi, cận an toàn kháng va chạm này tốt hơn so với các hàm nén khác. Ngoài ra, chúng tôi đã đưa ra phân tích độ an toàn kháng tiền ảnh của Alpha-DBL cho thấy cận an toàn là 2 truy vấn cho . Sử dụng lược đồ này trong việc xây dựng hàm băm được lặp có thể bảo toàn độ an toàn kháng va chạm và an toàn kháng tiền ảnh.